Analisis Dampak Pengenalan "Coding Skills" dalam Meningkatkan Minat Pendidikan Tinggi Siswa SDN Tanjungsari 2 - Maulidya, Utsna Rosalin; Dita Amelia (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
Merdeka Belajar Kampus Merdeka (MBKM) a policy through the Teaching Assistance (AM) program opens opportunities for students to act as agents of change, one of which is by assisting schools in adapting technology. Specifically in the subject of Information and Communication Technology (ICT). This study aims to analyze the impact of introducing basic "Coding Skill" on improving students' understanding and interest in computational thinking skills, as well as their motivation to continue to higher education. This AM activity was carried out at SDN Tanjungsari 2 with 26 sixth-grade students for a total of 27 face-to-face meetings, or approximately two months. Students applied an interactive learning system through hands-on practice using programming software such as OSR-R and ScratchJr. The learning method was adjusted to address the characteristics of sixth-grade students, who tend to lack focus and get bored easily. Techniques such as visual demonstrations, interactive discussions, and rewards were used. The results of the study using a paired t-test showed that there was a significant difference between the pre-test and post-test results. This means that learning coding can increase students' interest and motivation to continue on to higher education. Students' understanding of the new ICT material they have learned has also improved significantly. All students also unanimously agreed that learning programming is exciting, so they are interested in exploring it further because they understand the benefits of higher education itself. This interactive method successfully overcomes the problem of students' lack offocus and increases their enthusiasm for learning. In addition, this program also contributes to accelerating Sustainable Development Goal (SDG) 4, which is the achievement of quality education.